Effects of Plant Spacing on Yields and Nutritive Values of Napier Grass (Pennisetum purpureum Schum.) Under Intensive Management of Nitrogen Fertilizer and Irrigation - Wijitphan, Sumran; Lorwilai, Pornchai; Arkaseang, Chutipong (Pakistan Journal of Nutrition, 2009)
There was a significant effect of plant spacing on total dry matter yield among 50 x 40, 50 x 40, 50 x 40 and 50 x 100 cm plant spacing of Napier Grass. The highest total dry matter yield of 70.84 t ha-1 was obtained from 50 x 40 planting configuration. There was significant effect of plant spacing on dry matter production of the grass from 8 harvests. In a 50 x 40 planting configuration, the range of dry matter production from 11 harvests was 2.6-10.19 t ha-1. Plant spacing did not have significant (p>0.05) effect on Crude Protein (CP), Acid Detergent Fiber (ADF) and Dry Matter Digestibility (DMD) but Neutral Detergent Fiber (NDF) was significantly affected (p